Diversity of Ralstonia Solanacearum in Cameroon and genetic basis of resistance of pepper (Capsicum Annuum L.) and Solanaceae - (:unkn) unknown (My University, 2010)
The knowledge of genetic diversity of R. solanacearum as well as the knowledge of genetic determinism of pepper resistance are critical for elaborating a strategy against this ubiquist bacterium. They will facilitate the choice and direction of fighting methods and the development of well adapted tools for quarantine measures. In a modern approach of genetics more and more based on plant models, Solanaceaes occupy a place of pioneer. On another hand the emerging breakdown of resistances seems to be due to large genotypic and phenotypic diversity of R. solanacearum. In such a context, the objective of this thesis is to set up the basis for an improvement programme of Solanaceous species against this major bacterial disease in Cameroon. A molecular methodology was used, namely the phylophasic characterization method, which describes R. solanacearum genetic diversity into four phylotypes and sequevars. We have revealed the existence of three phylotypes in this African country where agro-climatic diversity makes it named "Africa in miniature". These phylotypes are : I (Asiaticum), II (Americanum) and III (Africanum). The strains of phylotype III from Cameroon are genetically distinct from African reference strains originating from Zimbabwe and Indian Ocean. The strains isolated on potato plants from the highlands in Western Cameroon belong to both phylotypes II (r3-bv2) and III. Strains of phylotype II and III from Western highlands can infect potato as well as the tomato plants. They constitute an economic threat for these crops in this mountainous area (AEZ3 : Foumbot, Baham, Dschang, Mbouda, Bafoussam, Bamougoum). In our study, strains of phylotype I emerge in wet forests zone (AEZ5 : Yaoundé, Obala, Okola, Akonolinga, Bafia) and represent a major threat for Solanaceous crops. This statement directed the choice of a strain from phylotype I, CMR143, in further work on genetic mapping. Consequently, two district pepper genitors of resistance were used, n
Keywords: African Research